The Molecular Landscape of Primary Acral Melanoma: A Multicenter Study of the Italian Melanoma Intergroup (IMI) - Elefanti, Lisa (Int J Mol Sci, 2021)
Acral melanoma (AM) is a rare and aggressive subtype of melanoma affecting the palms, soles, and nail apparatus with similar incidence among different ethnicities. AM is unrelated to ultraviolet radiation and has a low mutation burden but frequent chromosomal rearrangements and gene amplifications. Next generation sequencing of 33 genes and somatic copy number variation (CNV) analysis with genome-wide single nucleotide polymorphism arrays were performed in order to molecularly characterize 48 primary AMs of Italian patients in association with clinicopathological and prognostic features. BRAF was the most commonly mutated gene, followed by NRAS and TP53, whereas TERT promoter, KIT, and ARID1A were less frequently mutated. Gains and losses were recurrently found in the 1q, 6p, 7, 8q, 20 and 22 chromosomes involving PREX2, RAC1, KMT2C, BRAF, CCND1, TERT, and AKT3 genes, and in the 6q, 9, 10, 11q and 16q chromosomes including CDKN2A, PTEN, and ADAMTS18 genes, respectively. This study confirmed the variety of gene mutations and the high load of CNV in primary AM. Some genomic alterations were associated with histologic prognostic features. BRAF mutations, found with a higher rate than previously reported, correlated with a low Breslow thickness, low mitotic count, low CNV of the AMs, and with early-stage of disease.